2021
DOI: 10.3390/f12101369
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Mode I Fracture Behaviors of Wood Using Compact Tension in Selected System Crack Propagation

Abstract: The fracture behaviors of four wood species commonly used in wood products were characterized when subjected to compact tension (CT) load in radial-longitudinal (RL) system crack propagation. Meanwhile, the failure modes of evaluated CT samples were compared and analyzed using the fractal dimension method. The results showed that wood species had a significant effect on fracture characteristic values, including maximum fracture load, critical stress intensity factor and fracture energy. These characteristic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Machines 2022, 10, x FOR PEER REVIEW 2 of 12 speed, tool angle and cutting direction [10,11], and that surface roughness is an important part for final product quality and guaranteed product commercial value [12]. Milling is the most commonly used processing method for wood machining for outstanding machining efficiency [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Machines 2022, 10, x FOR PEER REVIEW 2 of 12 speed, tool angle and cutting direction [10,11], and that surface roughness is an important part for final product quality and guaranteed product commercial value [12]. Milling is the most commonly used processing method for wood machining for outstanding machining efficiency [13].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, changes in surface roughness were investigated by Sütçü and Abdullah [9], and their study indicated that feeding speed and cutting direction are two parameters affecting surface smoothness during beech wood machining. In general, surface roughness is affected predominantly by material properties, cutting speed, tool angle and cutting direction [10,11], and that surface roughness is an important part for final product quality and guaranteed product commercial value [12].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal cutting parameters determined in this study were rake angle 2 • , cutting speed 9.0 m/s, feed per tooth 0.3 mm, and cutting depth 1.5 mm. This is in contrast to traditional wood materials [20][21][22][23]. Optimal cutting parameters for WPC yielding the lowest surface roughness were determined to include a higher rake angle and cutting speed, at a lower feed per tooth and cutting depth.…”
Section: Optimal Cutting Parameters For Wood-plastic Composite Machiningmentioning
confidence: 99%
“…As a natural polymer heterogeneous composite material [1], wood has always been favored by people and has always maintained an important position in the field of building decoration materials [2]. However, due to changes in environmental factors [3], wood's wet expansion and dry shrinkage [4], insufficient film toughness [5] and mismatches with the wood's interface [6], cracks appear in the film during use [7,8], which reduces the sealing performance and leads to film failure. Microcapsule technology is widely used in coatings, wood products, furniture, agriculture and so on.…”
Section: Introductionmentioning
confidence: 99%